2007
DOI: 10.1136/gut.2007.122739
|View full text |Cite
|
Sign up to set email alerts
|

Risk of progression of advanced adenomas to colorectal cancer by age and sex: estimates based on 840 149 screening colonoscopies

Abstract: Objectives: To derive age and sex specific estimates of transition rates from advanced adenomas to colorectal cancer by combining data of a nationwide screening colonoscopy registry and national data on colorectal cancer (CRC) incidence. Design: Registry based study. Setting: National screening colonoscopy programme in Germany. Patients: Participants of screening colonoscopy in 2003 and 2004 (n = 840 149). Main outcome measures: Advanced adenoma prevalence, colorectal cancer incidence, annual and 10 year cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
272
0
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(294 citation statements)
references
References 23 publications
10
272
0
12
Order By: Relevance
“…Data on stage distribution and stage-specific crc survival were obtained from Canadian sources 12 . Another review of the literature identified information about adenomatous polyp prevalence, incidence, growth rates, variation by sex, size, site distribution, and histology [13][14][15][16][17][18][19][20][21][22][23][24] . Where possible, the literature was used to directly estimate parameters for the model; otherwise, it was used to inform parameter values for the model through calibration and provision of targets.…”
Section: Natural History Modelmentioning
confidence: 99%
“…Data on stage distribution and stage-specific crc survival were obtained from Canadian sources 12 . Another review of the literature identified information about adenomatous polyp prevalence, incidence, growth rates, variation by sex, size, site distribution, and histology [13][14][15][16][17][18][19][20][21][22][23][24] . Where possible, the literature was used to directly estimate parameters for the model; otherwise, it was used to inform parameter values for the model through calibration and provision of targets.…”
Section: Natural History Modelmentioning
confidence: 99%
“…The development of advanced adenomas may take less time that that of CRC. In addition, the 10-year cumulative risk of progressing from advanced adenoma to CRC is estimated to be less than 50% in individuals 55 years or older (Brenner et al, 2007). Second, the frequency of patients with right-sided CRC in the second study was much higher compared to the number of patients with right-sided advanced neoplasms in the first study, resulting in better statistics.…”
Section: Crc Incidence In Screening Cohortsmentioning
confidence: 92%
“…Advanced adenomas have been considered to be the clinical precursors of CRC; however, we have to take into account that available estimates for the progression of adenomas were mostly derived from radiological surveillance data or from autopsy series collected prior to the colonoscopy era. Since advanced adenomas need to be removed once they are detected, any direct observation of their natural history would be unethical [18].…”
Section: Definition Of a False-positive Results In Crc Screeningmentioning
confidence: 99%